2017
DOI: 10.3382/ps/pew270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on the occurrence of muscle fiber degeneration associated with myopathies in broiler chickens submitted to feed restriction

Abstract: To evaluate muscle fiber degeneration (MFD) associated with white striping and wooden breast, pectoralis major of 192 broilers differing for genotype (standard vs. high breast yield), gender, and feeding regime (ad libitum vs. restricted rate 80% from 13 to 21 d of age) were sampled at 14, 21, 28, 35, and 46 d of age for histological analyses by hematoxylin and eosin (H&E) staining to evaluate tissue morphology, Masson's trichrome to identify collagen presence, and Oil red and Nile blue for lipid presence. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
61
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 22 publications
16
61
0
1
Order By: Relevance
“…It is widely accepted that the incidence of breast abnormalities rises with increasing slaughter weight (Cruz et al, 2016;Lorenzi et al, 2014;Papah et al, 2017), growth rate (Kuttappan et al, 2012a(Kuttappan et al, , 2013a(Kuttappan et al, , 2017Lorenzi et al, 2014), and genetic potential for breast meat yield (Alnahhas et al, 2016;Bailey et al, 2015;Livingston et al, 2018;Lorenzi et al, 2014;Petracci et al, 2013;Trocino et al, 2015) in agreement with strong genetic correlations found by Alnahhas et al (2016). This has been also confirmed by histological observations which evidenced that myodegeneration progress associated with the development of breast abnormalities is strictly related to age at slaughter (Griffin et al, 2018;Kawasaki et al, 2018;Papah et al, 2017;Radaelli et al, 2017;Sihvo et al, 2017) and breast growth pattern (Papah et al, 2017) (Table 5; Radaelli et al, 2017). Recently, it was also demonstrated that egg storage duration before hatching as well as manipulation of embryonic development by egg incubation temperatures and chick weight at hatching can affect muscle morphology traits and related to occurrence of breast abnormalities (Clark, Walter, & Velleman, 2017;Livingston et al, 2018).…”
Section: Means Of Alleviation: Facts and Challengessupporting
confidence: 57%
See 1 more Smart Citation
“…It is widely accepted that the incidence of breast abnormalities rises with increasing slaughter weight (Cruz et al, 2016;Lorenzi et al, 2014;Papah et al, 2017), growth rate (Kuttappan et al, 2012a(Kuttappan et al, , 2013a(Kuttappan et al, , 2017Lorenzi et al, 2014), and genetic potential for breast meat yield (Alnahhas et al, 2016;Bailey et al, 2015;Livingston et al, 2018;Lorenzi et al, 2014;Petracci et al, 2013;Trocino et al, 2015) in agreement with strong genetic correlations found by Alnahhas et al (2016). This has been also confirmed by histological observations which evidenced that myodegeneration progress associated with the development of breast abnormalities is strictly related to age at slaughter (Griffin et al, 2018;Kawasaki et al, 2018;Papah et al, 2017;Radaelli et al, 2017;Sihvo et al, 2017) and breast growth pattern (Papah et al, 2017) (Table 5; Radaelli et al, 2017). Recently, it was also demonstrated that egg storage duration before hatching as well as manipulation of embryonic development by egg incubation temperatures and chick weight at hatching can affect muscle morphology traits and related to occurrence of breast abnormalities (Clark, Walter, & Velleman, 2017;Livingston et al, 2018).…”
Section: Means Of Alleviation: Facts and Challengessupporting
confidence: 57%
“…(). This has been also confirmed by histological observations which evidenced that myodegeneration progress associated with the development of breast abnormalities is strictly related to age at slaughter (Griffin et al., ; Kawasaki et al., ; Papah et al., ; Radaelli et al., ; Sihvo et al., ) and breast growth pattern (Papah et al., ) (Table ; Radaelli et al., ). Recently, it was also demonstrated that egg storage duration before hatching as well as manipulation of embryonic development by egg incubation temperatures and chick weight at hatching can affect muscle morphology traits and related to occurrence of breast abnormalities (Clark, Walter, & Velleman, ; Livingston et al., ).…”
Section: Means Of Alleviation: Facts and Challengesmentioning
confidence: 67%
“…Healthy unaffected muscle tissue is a well‐organised structure with long multinuclear muscle fibres. This organisation is disrupted in PMs with WB, where substitution of muscle tissue by fibrotic and adipose tissue has been reported (Petracci et al ., ; Sihvo et al ., ; Radaelli et al ., ), which is consistent with our results. Previous studies on WB tissue show that the number of fibres is reduced and that the fibres are more variable in size and are more often separated by or replaced by fibrotic tissue (Sihvo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The high productive of poultry as a result of a constant increase in the world demand for white meat with a intensive genetic selection for fast growth rate and high breast yield, have been spurring the broiler industry towards practices that increase its production [1][2][3], and these factors may induce metabolic stresses that can negatively impact meat quality [4][5][6]. More recently, high growth rate and high breast yield have been associated with the occurrence of other myopathies affecting pectoralis major and other muscles, i.e., white striping [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Feeding strategies may be used to control de occurrence of myopathies in broiler chickens: low-energy diets reduce both growth rate and the occurrence of white striping [11], however the correlation between the occurrence of this myopathy and growth rate/final live weight and/or breast yield in current broiler genotypes under commercial intensive conditions has been proposed but not fully demonstrated [3]. Bailey et al [12] also described that the analysis of data from two broiler lines that differed in terms of selection for breast yield showed that there is also a strong non-genetic component for all breast muscle myopathy traits.…”
Section: Introductionmentioning
confidence: 99%